Pre-climax epiphyte communities of bryophytes and lichens in Mediterranean forests from the Central Plateau (Spain) (Plant Ecology, 1996)
The pre-climax epiphytic communities of forests from the Spanish Mediterranean region (Central Plateau) were studied by numerical and traditional floristic methods. One hundred phytosociological relev6s were analyzed through a classical numerical approach based on hard partitions improved by PCoA - Principal Coordinates Analysis - ordinations. Two groups easily related to two different suballiances included in Frullanion dilatatae Lecointe 1975, Ulotenion crispae (Barkman 1958)Lecointe 1975 and Fabronienionpusillae Barkman 1958 were detected. Two new syntaxa within the ass. Ortotrichetum lyeUii (Allorge 1922) Lecointe 1975 are proposed. Phytogeography, syntaxonomy and ecology of these communities are discussed.